Decrease of Plasma Glucose by Hibiscus taiwanensis in Type-1-Like Diabetic Rats. (17th April 2013) - Wang, Lin-Yu; Chung, Hsien-Hui; Cheng, Juei-Tang
Abstract : Hibiscus taiwanensis (Malvaceae) is widely used as an alternative herb to treat disorders in Taiwan. In the present study, it is used to screen the effect on diabetic hyperglycemia in streptozotocin-induced diabetic rats (STZ-diabetic rats). The extract of Hibiscus taiwanensis showed a significant plasma glucose-lowering action in STZ-diabetic rats. Stems of Hibiscus taiwanensis are more effective than other parts to decrease the plasma glucose in a dose-dependent manner. Oral administration of Hibiscus taiwanensis three times daily for 3 days into STZ-diabetic rats increased the sensitivity to exogenous insulin showing an increase in insulin sensitivity. Moreover, similar repeated administration of Hibiscus taiwanensis for 3 days in STZ-diabetic rats produced a marked reduction of phosphoenolpyruvate carboxykinase (PEPCK) expression in liver and an increased expression of glucose transporter subtype 4 (GLUT 4) in skeletal muscle. Taken together, our results suggest that Hibiscus taiwanensis has the ability to lower plasma glucose through an increase in glucose utilization via elevation of skeletal GLUT 4 and decrease of hepatic PEPCK in STZ-diabetic rats.